Exploring of Quran Illiteracy in Several Hamlets, Celawan Village, Pantai Cermin District, Serdang Bedagai Regency - Mardian Idris Mardian; Muhammad Yoggie Ramadhan Sahputra; Gian Maulana Araddu; Raydatul Maqfirah; Cindy Mutiara P (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Nahdlatul Ulama Blitar, 2022)
Al-Qur'an illiteracy is not being able to understand and read the Qur'an properly and correctly based on the rules of reading the Qur'an, namely Tajweed. The government has launched a program to eradicate illiteracy, including the Koran script. The ability to read the Koran in the Economics of Parents Against Blind Indonesia is currently still weak and the literacy of school-age children is low. Based on survey data, Sumber Wringin District. Carried out by DMI (Indonesian Mosque Council) said that, because of the Indonesian factor, only 35% of the people of Celawan were socially marginalized in reading the Koran in Indonesia. The matter of society and economic inclusion was conveyed by the deputy chairman into the general category of DMI, Komjen Pol Syafruddin. People's inability to work makes them less concerned about reading the Qur'an and is very concerned about religious education. The program will be implemented in destroying or eradicating the blindness of the writing system and ways of reading the Koran. For the children of Celawan Village, the majority of which are vegetable farmers and rice farmers, they still help their parents in the fields and play after school. Purpose of this Research is to find out the methods and constraints of illiteracy in the Koran in order to solve the problem in Celawan Village. The approach used is descriptive qualitative research.